Memories of the II National Workshop of Experts in care of the Severely Ill Neonate - Elsa Martínez Sariol; Nadina Travieso Ramos; Annia Piña Montero (Centro Provincial de Información de Ciencias Médicas, 2018)
The II National workshop of Experts in care to the Severely Ill Neonate was developed from the May 28th to 30th, 2018, sponsored by the Chapter of the Cuban Society of Nursing, under the central topic, "Validation of the training strategy for the development of specific competences in the care to the severely ill neonate". With the participation of 38 experts of the neonatology specialty and 5 invited outstanding personalities of sciences in Cuba, the workshop marked the rules as for the proposed objectives, once the experts evaluated and validated in plenary session the specific competences of these professionals for the care to these new born, for the sake of guaranteeing the quality of the specialized medical care.